2021
DOI: 10.1186/s41938-021-00409-2
|View full text |Cite
|
Sign up to set email alerts
|

Effects of local isolates of Beauveria bassiana (Balsamo) Vuillemin on the two-spotted spider mite, Tetranychus urticae (Koch) (Acari: Tetranychidae)

Abstract: Background The two-spotted spider mite, Tetranychus urticae (Koch) (Acari: Tetranychidae), is a widely distributed plant-feeding pest that causes significant yield losses in a wide range of crops. Newly developed or improved environmentally friendly biocontrol agents serve as an alternative to traditional pest control tools. Experiment of the effects of 2 local fungal isolates of Beauveria bassiana (BGF14 and BCA32) was carried out against T. urticae under laboratory conditions. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
3
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 22 publications
1
3
0
1
Order By: Relevance
“…Yanar et al (2018) reported that the two isolates of F-12 and F-56 caused the maximum mortality of 78.3 and 76.7%, respectively at the conidial concentration of 1 × 10 8 conidia/ml, which showed similarity to the results of the present investigation. .03% mortality of T. urticae at the conidial concentration of 10 8 conidia/ml, which is analogous with the present results (Yucel 2021). At a spore concentration of 1 × 10 8 conidia/ ml in laboratory circumstances, the B. bassiana isolates PPRC 19, PPRC 27, PPRC 29, and PPRC 66 were moderately virulent against T. urticae, producing 60-80% death, which corresponds to the findings of the present study and the isolates 9614 and 9609 were highly virulent with the mortality range of 86-90% (Negash et al 2017), which is in further conformity to the present results as the isolate MZ749636 (B.b-7) resulted in 86.10% mortality of the two-spotted spider mite.…”
Section: Discussionsupporting
confidence: 92%
“…Yanar et al (2018) reported that the two isolates of F-12 and F-56 caused the maximum mortality of 78.3 and 76.7%, respectively at the conidial concentration of 1 × 10 8 conidia/ml, which showed similarity to the results of the present investigation. .03% mortality of T. urticae at the conidial concentration of 10 8 conidia/ml, which is analogous with the present results (Yucel 2021). At a spore concentration of 1 × 10 8 conidia/ ml in laboratory circumstances, the B. bassiana isolates PPRC 19, PPRC 27, PPRC 29, and PPRC 66 were moderately virulent against T. urticae, producing 60-80% death, which corresponds to the findings of the present study and the isolates 9614 and 9609 were highly virulent with the mortality range of 86-90% (Negash et al 2017), which is in further conformity to the present results as the isolate MZ749636 (B.b-7) resulted in 86.10% mortality of the two-spotted spider mite.…”
Section: Discussionsupporting
confidence: 92%
“…On the contrary, a negative F ST value has been considered equal to zero, indicating no population structure (Meirmans 2006). Wright (1978) suggested that FST values ranging from 0.05 and 0.15 indicate moderate genetic differentiation between pairs of populations. On the other hand, Nm (=number of migrants) estimates the gene-flow between populations (Whitlock and Mccauley 1999).…”
Section: Discussionmentioning
confidence: 99%
“…Ali et al (2020) reported that the mortality rates were 39.2% and 78.65% on the T. urticae 7 days after B. bassiana B1 and B2 isolates (1×10 8 spore/ml) were applied. Yucel (2021) investigated the lethal effects of B. bassiana BGF14 and BCA32 isolates (1×10 6 , 1×10 7 , and 1×10 8 spore/ml) on T. urticae. On the 7 DAA, at 10 6 , 10 7 , and 10 8 spore/ml doses of BGF14 isolate occurred 47.10±2.94%, 44.95±3.62% and 76.98±3.32% mortality, and these mortality rates were 63.06±1.95%, 81.09±4.10%, and 87.27±2.76% for BCA32 isolate.…”
Section: Pot Experimentsmentioning
confidence: 99%
“…In order to decide the most virulent isolate, pathogenicity of different isolates against the target pest must be determined (Zimmermann, 2007). Recent studies have recorded the effectiveness of different isolates of B. bassiana against T. urticae (Chandler et al, 2005;Draganova & Simova, 2010;Örtücü & Albayrak İskender, 2017;Yucel, 2021). These studies investigated the lethal effect of different spore concentrations on T. urticae.…”
Section: Introductionmentioning
confidence: 99%